1995
DOI: 10.1001/archinte.1995.00430180025004
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effectiveness of Interventions Intended to Help People Stop Smoking

Abstract: In a systematic review of the efficacy of interventions intended to help people stop smoking, data have been analyzed from 188 randomized controlled trials. Following personal advice and encouragement to stop smoking given by physicians during a single routine consultation, an estimated 2% (95% confidence limits, 1%, 3%; P < .001) of all smokers stopped smoking and did not relapse up to 1 year as a direct consequence of the advice. The effect is modest but cost-effective: the cost of saving a life is about $15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
0
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(166 citation statements)
references
References 104 publications
7
153
0
6
Order By: Relevance
“…Physicians in the clinic caring for transplant recipients with diabetes mellitus should also strive to have A1C measured regularly and direct therapy to control this measure at or below recommended targets (33). In addition to these strategies, repetitive attempts to encourage cessation of smoking with or without adjunctive therapy would also be worthwhile (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Physicians in the clinic caring for transplant recipients with diabetes mellitus should also strive to have A1C measured regularly and direct therapy to control this measure at or below recommended targets (33). In addition to these strategies, repetitive attempts to encourage cessation of smoking with or without adjunctive therapy would also be worthwhile (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Brief physician encouragement and counseling increases physical activity 1 and decreases smoking behavior. 2 Similarly, health-related quality of life (HRQoL) can be improved when physicians address conditions that cause impairment. [3][4][5] While there are differences between patient and physician reports of counseling, even during the same encounter, 6 physicians' rates of behavior change counseling for physical inactivity and tobacco use are low, regardless of the reporter and despite the clear need to address such behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking relapse rates remain disturbingly high, with approximately 50% of smokers relapsing within 3 days and 75% within the first 2 weeks (Garvey et al 1992;Law and Tang 1995;Rose 1996). Studies have shown that personality traits (e.g., related to depression and anxiety) may also predict risk for smoking relapse (Hall et al 1993;Hughes et al 1991;Killen and Fortmann 1997).…”
Section: Introductionmentioning
confidence: 99%